The oral health status of America's rural children: An opportunity for policy change - Crouch, Elizabeth; Nelson, Joni; Merrell, Melinda A.; Martin, Amy (Journal of public health dentistry, 2021)
Objectives The purpose of our study was to examine the association between rurality and select oral health care metrics: teeth condition, decay, and access measures such as preventive dental care among children in the United States. Methods We conducted a cross‐sectional study with a sample of 20,842 respondents from the 2017 to 2018 National Survey of Children's Health (NSCH), a nationally representative sample of U.S. children. Socio‐demographic information, residence, and oral health and healthcare utilization information were used to create study variables. Descriptive statistics, bivariate analyses, and a multivariable regression model were performed. Results Rural children were less likely to have a preventive dental visit than urban children (84.9 percent versus 87.5 percent, P = 0.03). Children residing in rural areas were more likely to have their teeth condition reported as fair or poor than children residing in urban areas (7.3 percent versus 6.6 percent, P = 0.02). Compared to their urban counterparts, rural children were also less likely to have received fluoride treatment (46.6 percent versus 52.5 percent, P = 0.0022) and less likely to have received a dental sealant (19.5 percent versus 22.5 percent, P = 0.0147). In adjusted analysis, there was no significant difference in receiving a preventive dental visit for rural children, compared to their urban counterparts. Conclusions As preparations are made for the 2020 Surgeon General's report on oral health, the current study provides important evidence to inform future advocacy and legislative priorities. To reduce urban–rural disparities among children, there must be enhanced dental care access, dental workforce expansion, and increased awareness about preventive oral health services.